1978
DOI: 10.1111/j.1432-1033.1978.tb12190.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of beta-Glucosidase Isoenzymes Possibly Involved in Lignification from Chick Pea (Cicer arietinum L.) Cell Suspension Cultures

Abstract: Crude cell wall preparations from Cicer urietinurn L. cell suspension cultures show high activity for the hydrolysis of coniferyl alcohol P-D-glucoside (coniferin). Various 0-glucosidase activities could be solubilized from these preparations by 0.5 M NaCl treatment and one of these could be shown to possess a high activity for the hydrolysis of coniferin. The enzyme activities were purified to near homogeneity by Sephadex G-200 and CM-Sephadex chromatography. Isoelectric focussing indicated the occurrence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0
1

Year Published

1981
1981
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 16 publications
0
26
0
1
Order By: Relevance
“…Other workers (17) have obtained similar data and have interpreted such results to indicate that the ,Bglucosidase is associated with the cell wall. Still other workers (9,16) have reported that cell wall fractions contain fi-glucosidases active on secondary plant products. When isolated cells of M. alba mesophyll were prepared and examined for the ,B-glucosidase, only a small fraction (7%) of the total activity was observed.…”
Section: Resultsmentioning
confidence: 99%
“…Other workers (17) have obtained similar data and have interpreted such results to indicate that the ,Bglucosidase is associated with the cell wall. Still other workers (9,16) have reported that cell wall fractions contain fi-glucosidases active on secondary plant products. When isolated cells of M. alba mesophyll were prepared and examined for the ,B-glucosidase, only a small fraction (7%) of the total activity was observed.…”
Section: Resultsmentioning
confidence: 99%
“…However, we have shown that the so-called "null" genotypes have ␤-glucosidase activity when assayed in solution. The enzyme is not detected on zymograms, because it occurs as large quaternary complexes whose native molecular masses may exceed 1.5 ϫ 10 6 Da. Furthermore, we have shown that the null phenotype is due to a 32-kDa protein called ␤-glucosidase-aggregating factor (BGAF) (GenBank TM AAF71261), which specifically binds and aggregates maize ␤-glucosidase, yielding high molecular weight complexes (12).…”
mentioning
confidence: 99%
“…They are found in all three (Archaea, Eubacteria, and Eukarya) domains of living organisms and play important roles in various biological processes, such as degradation of cellulosic biomass, hydrolysis of glycoconjugates, cyanogenesis, and modification of secondary metabolites (1). In plants, ␤-glucosidase activity is shown to be involved or implicated in several processes, such as defense against pathogens and herbivores (2-3), hydrolysis of phytohormones (4), floral development (5), lignification, and cell wall metabolism (6). In maize, two isozymes of ␤-glucosidase have been isolated and characterized with respect to structure, including three-dimensional structure, and function (7,8).…”
mentioning
confidence: 99%
“…For β-D-glucosidase detection, 4-methylumbelliferyl-β-D-glucuronide was added to a final concentration of 5 mM to the resolving gel mix [39]. After electrophoresis the enzyme protein band was visualized by staining with Coomassie brilliant blue R-250.…”
Section: Purification Of β-D-glucosidasementioning
confidence: 99%